Empowering Eight Through a Web-Based Repository System in Improving Student Research Performance - Kania, Raden; Solihati, Tifani Intan; Hidayanti, Nur; Bisri, Achmad; Roza Marmay; Edy Rakhmat (Teknik Informatika Universitas Pamulang, 2024)
Preliminary. The Banten Jaya University Library repository system still uses the conventional method of storing it on a shelf in the reference room, this makes it difficult for students who are completing their final project/thesis to access it online. Moreover, with the closure of the campus due to the COVID-19 pandemic, the PSBB and PPKM were continued. Research purposes. This research makes it easier for students to access library repository collections wherever they are, measure the extent of students' literacy skills in utilizing information sources, and show the impact on their research performance. Research methods. The data collection method uses a questionnaire, with statistical analysis, a model for assessing student literacy skills with Empowering 8, which is a research method used to produce products and test the effectiveness of these products, with the Waterfall system development model, which consists of analysis, design, implementation, and testing. Data Analysis. Metadata obtained from the repository application, distributing questionnaires to students taking Thesis/Final Project courses from each faculty. Results and Discussion. The literacy level of Banten Jaya University students is quite good, especially after the online repository has been built, there is a significant correlation between student literacy levels and student performance results. Conclusions and suggestions. A good literacy level is the basic capital in solving student problems while doing their research, it is necessary to have a Research Information Literacy program for students that is integrated with Research Methods courses so that student research performance increases in accessing the repository that has been built.